Perspectives on voice treatment for unilateral vocal fold paralysis. Issue 3 (June 2018) - Walton, Chloe; Carding, Paul; Flanagan, Kieran
Abstract : Purpose of review: Unilateral vocal fold paralysis (UVFP) is a common cause of neurogenic dysphonia resulting in glottal insufficiency. To restore glottal sufficiency and reduce the presenting dysphonia, treatment involving either surgical intervention, voice therapy or a combination of the two is typically provided. Currently, there is no consensus for the most effective voice treatment for UVFP. This results in an inability to compare current studies, and a lack of treatment effectiveness for the management of UVFP. This study aims to review the most recent literature for the management of dysphonia due to UVFP to establish the current evidence base for voice treatment options. Recent findings: There was found to be a lack of consistency in the rationale, selection and timing of the surgical intervention and/or voice therapy being provided for patients with UVFP. Summary: Further consensus is required for the rationale and selection of voice treatment prescriptions for the management of UVFP in order to improve treatment effectiveness and voice outcomes in patients with UVFP.